A Comparative Analysis of Factoring Market in Poland and the EU before and during the Time of COVID-19 - Maciej TOKARSKI (Communications of International Proceedings, 2020)
Factoring companies have been supporting Polish entrepreneurs in running their business for over 25 years. They finance their development and provide resources to meet the most urgent needs. They enable the conversion of receivables resulting from issued invoices into cash. This allows you to effectively secure financial liquidity and avoid payment gridlocks. Their services are already used by 22 thousand. companies in Poland. Factoring is the most dynamic section of the Polish financial services market, the volumes of factoring turnover has been steadily increasing since 2008. Unfortunately, the recent lockdown suppressed this dynamic trend and factoring was also affected by the slowdown. The present article is aimed at a comparative analysis of the factoring markets in Poland and UE.
Keywords: business financing; assignment of receivables; factoring market; Poland COVID-19